Electronic medical records for discovery research in rheumatoid arthritis - Liao, Katherine P. (2010)
OBJECTIVE: Electronic medical records (EMRs) are a rich data source for discovery research but are underutilized due to the difficulty of extracting highly accurate clinical data. We assessed whether a classification algorithm incorporating narrative EMR data (typed physician notes), more accurately classifies subjects with rheumatoid arthritis (RA) compared to an algorithm using codified EMR data alone. METHODS: Subjects with ≥1 ICD9 RA code (714.xx) or who had anti-CCP checked in the EMR of two large academic centers were included into an ‘RA Mart’ (n=29,432). For all 29,432 subjects, we extracted narrative (using natural language processing) and codified RA clinical information. In a training set of 96 RA and 404 non-RA cases from the RA Mart classified by medical record review, we used narrative and codified data to develop classification algorithms using logistic regression. These algorithms were applied to the entire RA Mart. We calculated and compared the positive predictive value (PPV) of these algorithms by reviewing records of an additional 400 subjects classified as RA by the algorithms. RESULTS: A complete algorithm (narrative and codified data) classified RA subjects with a significantly higher PPV of 94%, than an algorithm with codified data alone (PPV 88%). Characteristics of the RA cohort identified by the complete algorithm were comparable to existing RA cohorts (80% female, 63% anti-CCP+, 59% erosion+). CONCLUSION: We demonstrate the ability to utilize complete EMR data to define an RA cohort with a PPV of 94%, which was superior to an algorithm using codified data alone.